A spatiotemporal appraisal of road traffic accident in Kaduna metropolis, Nigeria - Muhammed, Abdulkadir Yahaya; Sani, Abdullahi Yusuf; Musa, Inusa; Ilyasu , Fatima Maaji; Suleiman, Umar Bambale; Oscar, Rowland; Muhammad, Abubakar Bawa; Uwanuakwa, Angela (Journal of Social, Humanity, and Education, 2021)
Purpose: Road accident has been claiming lives and no amount of research will be enough to expose the causes and dangers. This study appraises the causes and analyses the variation of road accidents in the Kaduna metropolis, intending to reduce it. Research methodology: The data used was obtained from Federal Road Safety Corps and complemented by the researchers’ field survey. Eight members of the research team went to the 24 bus stops identified each month rotationally. Both descriptive and inferential statistics were applied in the analysis. Results: There was a high correlation of mortality and road accident injuries as confirmed by r-value 0.7 using pearson product moment correlation. Accidents occur most in the morning and afternoon and the season with most accident occurrence was the dry season. The combination of over speeding and other factors were the major causes of road accidents. Limitations: The study used data published in 2016, although a follow-up data verification was conducted in 2017 and 2018. Therefore, the study is old and the results might have changed and might not necessarily be reliable. Contribution: Road accidents hot spots areas, causes, and patterns were exposed to guide the road users in order to avoid the accident. The study can also be replicated in other study areas with similar characteristics.